Barriers to Diaspora Communities’ Contribution to Indonesia’s Development - Ory Fahriansyah; Adityo Darmawan Sudagung (International Journal of Southeast Asian Studies (IJSAS), 2021)
This study aimed to explain the factors that cause the uneffective role of Indonesian diaspora in the development of the nation. The issue of diaspora continues to be a concern of Joko Widodo’s first term. However, over time, compared to the diaspora in China or India, the Indonesian diaspora has not played a very maximal role. We conducted a literature study by understanding each source text. The data were analysed using qualitative analysis based on the role theory and the concept of diaspora. This study found three important factors that determine the inhibiting role of the Indonesian diaspora, such as the dual citizenship factor, the understanding of Indonesian society which is still weak on the existence of the diaspora, and the connectivity factor.